Pursuing Rankings in the Age of Massification: For Most—Forget About It - Altbach, Philip G.; Hazelkorn, Ellen (International Higher Education, 2017)
Global rankings are aimed at the elite sector of higher education. This article argues that most universities worldwide should not pay attention to the rankings because it may distort the mission and activities of these institutions. In any case, they have no chance to score well in the rankings.